Cardiovascular manifestations in HIV-infected patients: a cross-sectional study from a tertiary care hospital - Rajan, Nayana; Paritekar, Anita (International Journal of Research in Medical Sciences, 2026)
Background: Human Immunodeficiency Virus (HIV) infection is associated with various cardiovascular manifestations, many of which remain asymptomatic and contribute significantly to morbidity. The present study was conducted to evaluate the prevalence and spectrum of cardiovascular manifestations among HIV-infected patients and to assess their association with CD4 counts and antiretroviral therapy adherence. Methods: This hospital-based cross-sectional study included 100 HIV-positive patients admitted to a tertiary care hospital between October 2019 and April 2021. Detailed clinical evaluation along with laboratory investigations including CD4 count, electrocardiography, chest radiography and two-dimensional echocardiography were performed in all patients. Coronary angiography was performed in selected patients when clinically indicated. Results: Cardiovascular abnormalities were observed in 48% of patients, of which 64.5% were asymptomatic. Diastolic dysfunction was the most common echocardiographic abnormality (36%), followed by systolic dysfunction (23%), dilated cardiomyopathy (11%) and pericardial effusion (9%). Lower CD4 counts and anemia were significantly associated with cardiovascular involvement. Conclusions: Cardiovascular manifestations are common in HIV-infected patients and often remain clinically silent. Routine cardiac evaluation, particularly echocardiography, may help in early detection of cardiac involvement in these patients.